Influence of Heat Transform and Rotation of Sutterby Fluid in an Asymmetric Channel - Mohammed, Asmaa A.; Hummady, Liqaa Zeki (Iraqi Journal of Science, 2023)
In this research, the effect of the rotation variable on the peristaltic flow of Sutterby fluid in an asymmetric channel with heat transfer is investigated. The modeling of mathematics is created in the presence of the effect of rotation, using constitutive equations following the Sutterby fluid model. In flow analysis, assumptions such as long wave length approximation and low Reynolds number are utilized. The resulting nonlinear equation is numerically solved using the perturbation method. The effects of the Grashof number, the Hartmann number, the Hall parameter, the magnetic field, the Sutterby fluid parameter, and heat transfer analysis on the velocity and the pressure gradient are analyzed graphically. Utilizing MATHEMATICA software, numerical results are computed. It is discovered that velocity varies with parameters, while the pressure gradient is directly proportional to most parameters.